PENENTUAN RESIDU PESTISIDA DELTAMETRIN DAN λ-SIHALOTRIN PADA LADA (Piper nigrum L.) MENGGUNAKAN METODE QuEChERS - Fitriadi, Bayu Refindra; Putri, Ayutia Ciptaningtyas (Indonesian Journal of Chemical Science, 2016)
The use of pesticides in agriculture especially pepper concern of residue accumulation, which may remain in the food and agricultural environment causing human health and damaging ecological balance. Beside that, pepper with high residue pesticide will be rejected by export destination countries. This study reported is based on the determination of deltamethrin and λ-cyhalothrin residue in pepper. Pepper was taken from supermarkets and pepper exporters in East Java. The pesticide residues were extracted and cleaned-up with optimalized QuEChERS method and determination was carried out on GC-ECD. Deltamethrin and λ-cyhalothrin respons have linear correlation with the concentrations at the range of 0.01 to 1.00 µg/mL (determination coefficient, r2, was 0.9993 and 0.9950). Detection and quantitation limits for deltamethrin were 0.020 µg/mL and 0.067 µg/mL, respectively, while detection and quantitation limits for λ-cyhalothrin  were 0.090 µg/mL and 0.301 µg/mL, respectively. Recoveries of these residues are between 99-143%. All pepper samples were tested, was undetected contain residues of λ-cyhalothrin and deltamethrin.